Data collection, analysis and recommendations - LIVE project (Deliverable 1) - Marco Raul Soares Amorim (2014)
The Deliverable describes the development within the LIVE project of a methodology for the record linkage between police data and hospital data, using the case study of the Porto region, Portugal. The importance of this process is well recognized by institutions such as IRTAD (OECD/ITF) that are promoting the combination of various data sources to fully assess the consequences of road accidents and monitoring progress. The complexity of this process is mainly concerned with several issues found in the data sets; mistakes and missing values are frequently detected and there are only a few common data fields that can be matched by the linkage process. The deliverable report explores the data issues usually present in this kind of data set that may influence the results of the linkage process. It is common in several countries/regions that each entity (e.g. hospital) presents a different data system, which imply several and distinct data treatments depending on data characteristics. There is already some international work done in this field, which is briefly described in this deliverable report. As it was concluded in those studies, developments and/or improvements are still needed. In Portugal, thus far, there is no database connecting the accident police data set and the injuries medical hospital information in which linked records may support several studies of the relationship between the accident sites characteristics and the injury severities. Under the LIVE project, for the first time, an approach was developed to link police and hospitals data sets covering the Porto region. In this work, a fixed deterministic and weight-based probabilistic method to link the police and hospital records was used. The results obtained lie within the range of rates found in other studies. Additionally, to improve the record linkage results, a validation process based on the emergency ambulance data was performed. Despite the missing values, it was possible to check 98% of the matched records as true matches. Finally, a preliminary investigation of bias after data linkage is described, showing that the variables selected for comparison indicate similar statistical values. In addition, a brief statistical analysis is presented using the linked records. Considering that one of the main objectives of the LIVE project is to assess the application to the Portuguese context of the common definition already established by the European Union - the maximum abbreviated injury scale (MAIS), a description of the actual Portuguese background is presented. Ongoing efforts are being carried out to reach this final objective. The road accident linkage process is clearly and deeply described in this report in order to be adapted, developed and applied in different contexts, aiming to promote future developments on police, hospital and emergency ambulance data either in Portugal or in other countries.